Schiff bases having a triazole ring bearing a pyridyl moiety are synthesized, and their biological activities are studied (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
The most frequently used organic compounds are Schiff bases. They have been demonstrated to have a broad variety of biological activities. Using a thermal method, the synthesis of a series of imine derivatives 4a-f from Amino triazole thiol (3) as starting material with six different aldehydes. Target compounds' full characterization was achieved using 1H and 13C- NMR, mass spectra, and FT-IR. In the 1H-NMR spectra of compounds (4a-f), an isotope with a proton signal for the CH of the azomethine group that ranged from 8 to 10.30 ppm was observed. Due to labile hydrogen bonds with nitrogen and sulfur, compound 3 exists in two tautomeric forms. Synthesis compounds' antibacterial activity was investigated against the bacteria Klebsiella, E. coli and, S. aureus.